Ischemic colitis and atrial septal aneurysm as a potential cause of systemic thromboembolism - Eihab A. Subahi (12217761) (2023)
Atrial septal aneurysm is a rare cardiac abnormality with thromboembolic potential and should be considered in a patient with ischemic colitis with no obvious risk factors. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.3889